MERCURY AS INDICATOR OF THE PRESENCE OF HYDROCARBONS - Ingovatov A.P.; Brovchuk I.F.; Borodin V.A. (My University, 1989)
The authors studied the behaviour of mercury and the forms of its occurrence in sediments overlying the pay during experimental work on gas content and biochemistry of rocks of the Udmurt oil fields. The geochemical samples for measuring the gas content of the surficial sandy-shaley sediments and for the determination of their Hg contents were taken from cores lifted from shallow (to 25 m) boreholes. The rocks overlying eight producing oilfields and three structures with an undefined oil potential were studied. The Hg sublimation curves of the geochemical samples indicate that in a zone of slow gas-water exchange Hg occurs in the greatest variety of forms because of its sulfidization. In this zone the dominant Hg forms are those with high sublimation temperatures. In the zone of active gas-water exchange, where sulfides are partially or completely oxidized and replaced by oxides of iron and maganese. Hg occurs in forms with low and average sublimation temperatures.